2009
DOI: 10.1371/journal.pone.0007806
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae Cytolysin Causes an Inflammatory Response in Human Intestinal Epithelial Cells That Is Modulated by the PrtV Protease

Abstract: Background Vibrio cholerae is the causal intestinal pathogen of the diarrheal disease cholera. It secretes the protease PrtV, which protects the bacterium from invertebrate predators but reduces the ability of Vibrio-secreted factor(s) to induce interleukin-8 (IL-8) production by human intestinal epithelial cells. The aim was to identify the secreted component(s) of V. cholerae that induces an epithelial inflammatory response and to define whether it is a substrate for PrtV.Methodology/Principal FindingsCultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Upregulation of IL-1␣, IL-1␤, TNF-␣, IL-8, and MCP-1 has been found in V. cholerae-infected fully differentiated T84 cells, whereas a striking dissimilarity in cytokine expression was observed in infected fully differentiated Caco-2 cells (759). The increased paracellular permeability and production of IL-8 and TNF-␣ in V. cholerae-infected fully differentiated T84 cells have been found to be triggered by the V. cholerae protease PrtV and V. cholerae cytolysin (VCC) (760).…”
Section: Host Cellular Defense Responsesmentioning
confidence: 99%
“…Upregulation of IL-1␣, IL-1␤, TNF-␣, IL-8, and MCP-1 has been found in V. cholerae-infected fully differentiated T84 cells, whereas a striking dissimilarity in cytokine expression was observed in infected fully differentiated Caco-2 cells (759). The increased paracellular permeability and production of IL-8 and TNF-␣ in V. cholerae-infected fully differentiated T84 cells have been found to be triggered by the V. cholerae protease PrtV and V. cholerae cytolysin (VCC) (760).…”
Section: Host Cellular Defense Responsesmentioning
confidence: 99%
“…Having found that V. cholerae induces neutrophil recruitment and a subset of proinflammatory factors in infant C57BL/6 mice at 24 to 30 h postinfection, we investigated bacterial factors that could contribute to the induction of inflammation. The toxins HlyA and RtxA are encoded within the genomes of all V. cholerae strains, regardless of whether they have acquired CTX, and have been implicated in inflammation with epithelial cells in vitro and in adult mouse models of V. cholerae infection (19,21,22,28). Mutants deleted for genes encoding RtxA or HlyA were investigated for PMN recruitment in infant mice.…”
Section: Inflammatory Markers Observed By Qrt-pcr In the Infantmentioning
confidence: 99%
“…In the infant rabbit model, flagellin-independent inflammation was still observed, suggesting that V. cholerae encodes other minor proinflammatory factors (16). In tissue culture models, purified V. cholerae O1 lipopolysaccharide (LPS) induces the proinflammatory transcription factor NF-B (18), and hemolysin A (HlyA) contributes to inflammation induced by non-O1/ non-O139 V. cholerae supernatants (19). Repeats toxin, encoded by rtxA and elaborated by the El Tor V. cholerae O1 biotype, but not the extinct classical biotype (20), was implicated in El Torinduced inflammation in an adult mouse pulmonary infection model (21), and both HlyA and RtxA are required for virulence in a mouse model of prolonged colonization (22).…”
mentioning
confidence: 99%
“…Therefore, it may be suggested that the presence of metalloprotease PrtV in CHA6.8 OMVs may be responsible for increased OMV-mediated cytotoxicity. However, earlier studies have shown that PrtV modulates IL-8 secretion from T84 cells (46). Interestingly, when cells were treated with CHA6.8 ⌬prtV, a shift from an apoptotic population to a necrotic population was observed.…”
Section: Discussionmentioning
confidence: 78%